“High-speed” Урбанізм. Розвиток житлового району “Під голоском” у Львові - Черкес, Богдан; Фенчук, Олександр; Cherkes, Bohdan; Fenchuk, Oleksandr (Видавництво Львівської політехніки, 2021)
Стаття присвячена дослідженню нового житлового району у м. Львові, що має назву Під Голоском. Описано процес формування району, від історичного до сьогодення та його участь у розвитку міста. На основі проведених досліджень визначено основні характеристики нового містобудівного утворення, кількість збудованого житла та перспективи його розвитку, чисельність населення, щільність забудови, забезпеченість закладами освіти та рекреацією. Досліджено основні урбаністичні характеристики району та явища, що супроводжують сучасні процеси містобудування в Україні.

The article is devoted to the study of a new residential area in Lviv, called Pid Holosko. It describes the process of formation of the district, from historical to the present day, and its participation in the development of the city. On the basis of the research identified the main characteristics of the new urban development, the number of houses built and the prospects for its development, the number of inhabitants, the intensity of buildings, the provision of educational institutions and recreation. The main urban characteristics of the region as well as phenomena that accompany present-day processes of urban development in Ukraine are investigated. The article is divided by the main types of urban characteristics into the stage of formation, indicators of residential construction and population, the state of social and infrastructural infrastructure and the forecasted prospective development. Problem statement. New residential suburb Holosko today is one of the largest housing estates in Lviv, with implementation rate growing day by day. The gradual development of such a city-building structure leads to problems such as: lack of educational institutions and social services, underdeveloped street and transport infrastructure, lack of parking spaces, the lack of public spaces and elements of sports infrastructure, etc. In order to solve these problems, an analysis of the processes of formation and current development of Pid Holosko is needed, with the aim of developing a comprehensive concept of the city's development. An analysis of recent research and publications. Up until now, the development of the residential microregion Pid Holosko has not actually been investigated. The main materials are the elaborated construction documents and the authors' own research. The planning structure and energy supply of the district at the municipal level was studied in the studies of L. Shuldan. The aim of this article is to investigate the peculiarities of formation of the new residential micro-district of Pid Holosko and to carry out an integrated analysis of its urban characteristics. On the basis of the conducted research the main problems associated with the fast pace of development of the area and the determination of its development trends in conditions of modern urban development processes were defined.].
High-speed urbanism. development of the residential district “Pid holoskom” in Lviv
Keywords: житловий район; житлова архітектура; сучасне містобудування; масове будівництво; житловий бум; “high-speed” урбанізм; residential area; residential architecture; modern urban development; mass construction; residential boom; high-speed urbanism; 711.42(477.83-25)